Assessing Transboundary Governance Capacity in the Great Lakes Areas of Concern - Greitens, Thomas J. (International Journal of Water Governance, 2016)
This case evaluates transboundary governance across the Great Lakes “Areas of Concern” (AOC). Designed with an emphasis on decentralization to sub-national institutions and the activation of citizen-led groups, the AOCs represent a unique approach to environmental governance.Traditionally examined with case study research, the individual AOCs are idiosyncratic with environmental and political challenges that are not always germane to other AOCs or broader theoretical concepts surrounding environmental governance. However, by examining the AOCs underlying transboundary governance architecture in terms of functional intensity, nature of compliance mechanisms, stability and resilience, and legitimacy a more comprehensive theoretical understanding ofthe successful governance processes used, as well as the gaps in governance responses observed, can be realized. The results presented here show that the AOCs can have significant transboundary governance weaknesses in terms of compliance mechanisms and notions of stability and resilience, but noteworthy strengths in terms of functional intensity and legitimacy. As a result, transboundary governance has a tendency to degrade over time in the AOCs, even though initial governance responses are initially effectively designed with high levels of stakeholder input.